Passing it up the ranks: hierarchical ion-size dependent supramolecular response in 1D coordination polymers - Schmitt, Wolfgang (My University, 2018)
The synthesis and structural characterisations of four 1D coordination polymers based on the 1,3,5-tris(4-carboxyphenyl)benzene (H3btb) and 2,4,6-tris(2-pyridyl)-1,3,5-triazine (2-tpt) ligands are reported: [MII(Hbtb)(2-tpt)]·xDMF, M = Zn (1), Ni (2), Mn (3) and Cd (4). The tridentate chelating mode of the 2-tpt ligand hinders the formation of polynuclear assemblies, leading to the recurrence of structurally related 1D motifs in all four compounds. Two distinct packing arrangements are obtained for the 1D motifs demonstrating how variable radii and coordination environments influence supramolecular interactions throughout the structures. Further, the nature of the metal ion influences respective orientations of interacting groups in the structures, illustrating the importance of ligand flexibility in coordination polymer design.
PUBLISHED